The Economic Impact of the Federal Credit Union Usury Ceiling - WOLKEN, JOHN D.; NAVRATIL, FRANK J. (Journal of Finance, 1981)
ABSTRACT This study measures the impact of the Federal credit union usury ceiling on consumer credit availability and loan rates. When binding, the ceiling keeps loan rates low, but it reduces credit union lending. There is also evidence that a binding loan rate ceiling affects the competitiveness of credit unions in the market for deposits. Although the Federal Credit Union Act specifically mandates federally chartered credit unions to be a source of low cost consumer credit and to promote thriftiness, it is not at all clear that the intent of the Act is served by a binding usury ceiling.